Dalin Dictionary - Språkbanken Text (University of Gothenburg, 2024)
Dalin, Anders Fredrik Ordbok Öfver svenska språket. Vol I-II. (Stockholm 1850-1853) is a 19th century dictionary digitized at Språkbanken. We have developed a morphology, a fullform lexicon, for this dictionary, as part of the Swedish Framenet++.

Dalin, Anders Fredrik Ordbok Öfver svenska språket. Vol I-II. (Stockholm 1850-1853) är en ordbok digitaliserad vid Språkbanken. Vi har utvecklat en morfologi, ett fullformslexikon, för Dalins ordbok, som en del i SweFN++.
Dalin Ordbok Öfver Svenska Språket
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik